2018
DOI: 10.1038/s41598-018-33233-0
|View full text |Cite
|
Sign up to set email alerts
|

Early heme oxygenase 1 induction delays tumour initiation and enhances DNA damage repair in liver macrophages of Mdr2−/− mice

Abstract: Multi drug resistance protein 2 knockout mice (Mdr2−/−) are a mouse model of chronic liver inflammation and inflammation-induced tumour development. Here we investigated the kinetics of early heme oxygenase 1 (HO-1) induction on inflammation, tumour development, and DNA damage in Mdr2−/− mice. HO-1 was induced by intraperitoneal injection of cobalt protoporphyrin IX (CoPP) twice weekly for 9 consecutive weeks. Immediately after HO-1 induction, liver function improved and infiltration of CD4+ and CD8+ T cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…TME macrophages in radiotherapy (9,10). Tumor-associated macrophages (TAMs) are a key component of TME and play an important role in accelerating cancer progression (11).…”
Section: M2 Macrophages Reduce the Radiosensitivity Of Head And Neck mentioning
confidence: 99%
“…TME macrophages in radiotherapy (9,10). Tumor-associated macrophages (TAMs) are a key component of TME and play an important role in accelerating cancer progression (11).…”
Section: M2 Macrophages Reduce the Radiosensitivity Of Head And Neck mentioning
confidence: 99%
“…Interestingly, CoPP treatment was showed to limit cell proliferation in NG media, but not in HG media, after 5 days exposure. This was unexpected, since in the absence of any other stimulus the additions of CoPP are known not to have any effect on cell proliferation; although CoPP had recently been demonstrated to delay tumor growth (Barikbin et al 2018 ). CoPP treatment also significantly decreased the migration rate of HaCaT cultured in NG media, as opposed to when the cells were cultured in HG media, in which the CoPP had significantly enhanced migratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we showed that overexpression of HO-1 decreases tumorigenicity in secondary and tertiary recipients, probably due to reduced self-renewal of melanoma cells. Early induction of HO-1 in Mdr2 −/− mice (the model of chronic liver inflammation and inflammation-induced tumor development) delayed the initiation of liver tumors through amelioration of chronic inflammation [ 86 ]. Moreover, in chemically induced squamous cell carcinoma, HO-1 KO mice developed lesions earlier than WT animals [ 87 ], suggesting that HO-1 can delay the initiation of tumor formation.…”
Section: Discussionmentioning
confidence: 99%